2018
DOI: 10.1542/hpeds.2017-0183
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Observational Study on High-Value Care Topics Discussed on Multidisciplinary Rounds

Abstract: Despite a recent focus on improving health care value and educating trainees in the practice of HVC, our study demonstrated that bedside discussions of HVC are occurring with a limited frequency at our institution and that attending physicians initiate the majority of discussions. The capacity of the nonphysician team members to contribute to establishing and sustaining an HVC culture may be underused. Multi-institutional studies are necessary to determine if this is a national trend and whether discussions ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Of these, only 31% of HVC discussions were initiated by a trainee (resident or medical student) and fewer than half (41%) of HVC discussions were initiated by attending physicians or fellows. 27 Successful HVC curricula need to provide a foundation for knowledge transmission; however, additional supports, including faculty development in which informal HVC education is addressed and broader educational efforts to address the institutional culture of value and hidden curriculum, are necessary.…”
Section: Problem Identificationmentioning
confidence: 99%
“…Of these, only 31% of HVC discussions were initiated by a trainee (resident or medical student) and fewer than half (41%) of HVC discussions were initiated by attending physicians or fellows. 27 Successful HVC curricula need to provide a foundation for knowledge transmission; however, additional supports, including faculty development in which informal HVC education is addressed and broader educational efforts to address the institutional culture of value and hidden curriculum, are necessary.…”
Section: Problem Identificationmentioning
confidence: 99%
“…The findings of Beck et al 13 reinforce the need to further develop physician leaders as role-models and teachers of HVC. We have come to understand that the practice and behaviors learned in training often carry forward into clinical careers, 15 and the authors of several recent studies have identified a lack of supervisor role models as a factor driving low-value care for residents.…”
mentioning
confidence: 84%
“…As institutions and physicians determine how best to encourage HVC, the findings of Beck et al 13 support the idea that formal curricula are necessary but likely not sufficient. We should strive to expand the HVC educational environment beyond the lecture hall to include any place where patient care occurs.…”
mentioning
confidence: 92%
See 2 more Smart Citations